Improving Medication Adherence of Pulmonary Tuberculosis Patients with Health Coaching: Scoping Review - Setiyowati, Eppy; Subairi, Moh (Chakra Brahmanda Lentera Institute, 2024)
Background: One of the most important ways to ensure the success of tuberculosis treatment is to increase patient adherence to treatment to prevent infection, achieve a cure, and avoid drug resistance, recurrence, and death. The purpose of the literature review is to determine the importance of health coaching in improving treatment adherence in pulmonary tuberculosis patients. Methods: The stage of Scoping Review is to select journals by taking into account the year of publication and full text. Furthermore, articles and journals that are considered less relevant are excluded. Literature was obtained from 6 pertinent articles on Google Scholar, Indonesia One Search, DOAJ, and Garuda, with the keywords Health Coaching, Medication Adherence, and Tuberculosis. Results: After a review of the selected articles, the results of Health Coaching show that it has a good impact on improving medication adherence in pulmonary tuberculosis patients. Conclusion: Health coaching is effective in improving medication adherence among pulmonary tuberculosis patients. By equipping patients with the necessary knowledge, skills, and confidence, health coaching enhances self-management, supports better treatment outcomes, and helps prevent drug resistance, recurrence, and mortality.